2008
DOI: 10.1002/jbio.200810005
|View full text |Cite
|
Sign up to set email alerts
|

Membrane transport enhancement of chlorin e6‐polyvinylpyrrolidone and its photodynamic efficacy on the chick chorioallantoic model

Abstract: We have determined the influences of polyvinylpyrrolidone (PVP) on the topical delivery of chlorin e6 (Ce6) in malignant bladder cells. The chick chorioallantoic membrane (CAM) was used to model the tumor spheroids that resemble small residual bladder tumors prior to vascularization. Macroscopic fluorescence imaging showed that Ce6-PVP-induced fluorescence had a higher sensitivity and specificity for delineating tumor from the adjacent normal CAM compared to Ce6 alone. Nonlinear regression analyses have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For example, the topical application of chlorines showed a larger occlusion at 10 J/cm 2 doses with irradiance of 10 mW/cm 2 when compared to 15 and 20 J/cm 2 (with 15 and 20 mW/cm 2 , respectively). This difference for high doses may be related to the depletion of oxygen or faster photobleaching [43].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the topical application of chlorines showed a larger occlusion at 10 J/cm 2 doses with irradiance of 10 mW/cm 2 when compared to 15 and 20 J/cm 2 (with 15 and 20 mW/cm 2 , respectively). This difference for high doses may be related to the depletion of oxygen or faster photobleaching [43].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of Ce6-PVP was more than 80%, however, the specificity remained low. We have recently reported that the new formulation of Ce6-PVP (> 95% purity level of active Ce6) demonstrated a higher sensitivity (98%) and specificity (82%) on the CAM model [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…By employing a chick chorioallantoic membrane model, Ce6-PVP was shown to selective accumulate in bladder tumors xenografts and had a faster clearance from normal CAM when administered topically compared to systematic administration [ 14 ]. The uptake ratio of Ce6-PVP was found to have a 2-fold increase across the CAM when compared to that of Ce6, indicating that PVP was able to facilitate diffusion of Ce6 across the membrane [ 15 ]. Furthermore, Ce6-PVP had less in vivo systemic phototoxic effect compared to Ce6 alone after light irradiation in photodynamic therapy in mice bearing tumors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CAM continues to be a common in vivo model used to study tumor angiogenesis, anti-angiogenic drugs, [89][90][91][92][93][94] tumor vascular targeting, 95 metastasis, 96 97 ion transport, 98 allergens, 99 transplantation, 100 contraceptives, 101 102 effects of hyperglycemia, 103 and photodynamic therapy. 104 Since the CAM capillary network is so dense, it is comparable to the capillary plexus of the eye; 105 therefore, it has been extensively used as an ocular model 106 for photodynamic therapy (PDT) with photosensitizing drugs. 107 109 In addition, the CAM was initially used as an alternative to the Draize test, which originally involved exposing the eyes of rabbits to chemicals to determine irritation.…”
Section: Chorioallantoic Membrane (Cam)mentioning
confidence: 99%